ON THE ISSUE OF PREPARING THE FUTURE MEDICAL SPECIALISTS - O.V. Denysenko; I.L. Fomina (Academy of Cognitive and Natural Sciences, 2006)
Different aspects of activating o f future professional activity of student-medicians are discussed.